DESIGN AND IMPLEMENTATION OF DESCHMAN INTELLIGENT DOOR LOCK SALES WEBSITE - Lin, Li-Wei; Hsu, Chih-Fu; Lu, Kuo-Liang; Zheng, Zhi-Peng (International Journal of Research -GRANTHAALAYAH, 2023)
In the past five years, the rapid progress of science and technology has also spurred the rapid rise of the economy, and the people's income level has also made significant progress and changes. Therefore, there is an urgent need for a high-quality living standard. In such a superior environment, the smart home products industry also came into being and quickly gained a foothold. As one of the most popular products, intelligent door lock has gradually entered the public's vision. However, due to its high customer unit price and customers' concerns about safety, it has brought great challenges to the promotion and sales of intelligent door locks. Making a professional sales website has naturally become one of the important means to establish brand image, improve customer trust and increase product sales.